أثر متطلبات الإدارة الإلكترونية في تحسين جودة الخدمة الأكاديمية لجامعة الأقصى بغزة _ فلسطين: THE EFFECT OF ELECTRONIC ADMINISTRATION REQUIREMENTS ON IMPROVING THE QUALITY OF EDUCATIONAL SERVICES AT AL-AQSA UNIVERSITY IN GAZA -PALESTINE - Fora, Mohammed N.; Hashim, Osamah Yahya; Abd Aziz, Sumaiyah; Sharom, Qamarina; Abu Shawish, Abdul Karim (I-iECONS e-proceedings, 2023)
: هدفت الدراسة الحالية إلى التعرف على أثر متطلبات الإدارة الإلكترونية في تحسين جودة الخدمة الأكاديمية في جامعة الاقصى بفلسطين، تم الاعتماد على المنهج الوصفي التحليلي لإجراء الدراسة لملائمته لأغراض وطبيعة الدراسة وأهدافها، حيث استخدمت الاستبانة كأداة رئيسة لجمع البيانات من مجتمع الدراسة المكون من العاملين ذوي المسميات الإشرافية في الجامعة محل الدراسة (إداري بمنصب إشرافي، أكاديمي، أكاديمي بمنصب إداري) تم استخدام أسلوب العينة العشوائية الطبقية تبعاً للمسمى الوظيفي، حيث بلغ الحد الأدنى لمجتمع الدراسة الممثل عن المجتمع ما قيمته (234) مفردة وقد تم توزيع (250) استبانة، تم استرداد (238) بنسبة استجابة (90%). حيث توصلت الدراسة إلى أن مستوى توافر متطلبات الإدارة الإلكترونية في جامعة الأقصى بدرجة كبيرة، وكان المتطلب الأمني هو الأبرز بنسبة وزن (77.9%)، تليه المتطلب التقني بنسبة وزن (76.0%)، ثم المتطلب المالي بنسبة وزن (75.8%)، وفي المرتبة الرابعة المتطلب البشري بنسبة وزن (75.3%)، وأخيرًا المتطلب الإداري بنسبة وزن (74.7%). وأظهرت أن كلاَ من المتطلب البشري، المتطلب المالي، والمتطلب الأمني تؤثر بشكل كبير في تحسين جودة الخدمة الأكاديمية في جامعة الأقصى بغزة. وأخيرًا، أظهرت نتائج الدراسة عدم وجود فروق ذات دلالة إحصائية بين متوسطات استجابات المشاركين حول متطلبات الإدارة الإلكترونية وجودة الخدمة الأكاديمية في جامعة الأقصى. في حين توصي الدراسة بضرورة حث الموظفين على المتابعة الإلكترونية للعمليات بشكل دائم بحيث تستطيع الجامعة تحديد نقاط قوتها وتعزيزها، ونقاط ضعفها ومعالجتها، كما أن عليها استغلال كافة إمكانياتها المتاحة للتنبؤ بالتهديدات المحيطة بها بشكل مستمر والتي تؤثر على أدائها لتحقيق الجودة الأكاديمية. وكذلك التركيز على تقديم الخدمات باستخدام أحدث التقنيات الإلكترونية. Abstract: The current study aimed to investigate the impact of electronic management requirements on enhancing the quality of academic services at Al-Aqsa University in Palestine. An analytical descriptive methodology was employed due to its suitability for the study's nature and objectives. A questionnaire served as the primary data collection tool, targeting the university staff holding supervisory positions (administrative, academic, academic with administrative roles). The sample selection followed a stratified random approach based on job titles, with a minimum study population size of 234 individuals. A total of 250 questionnaires were distributed, and 238 were retrieved, resulting in a 90% response rate. However, this study revealed that the availability of electronic management requirements at Al-Aqsa University was high. The security requirement had the highest weight percentage (77.9%), followed by the technical requirement (76.0%), the financial requirement (75.8%), the human requirement (75.3%), and finally, the administrative requirement (74.7%). The study also found that the human, financial, and security requirements significantly influenced the improvement of academic service quality at Al-Aqsa University in Gaza. Lastly, the study showed no statistically significant differences in participants' responses regarding electronic management requirements and the quality of academic services at Al-Aqsa University. The study recommends encouraging employees to continuously monitor and evaluate electronic processes to identify strengths and weaknesses. Additionally, the university should use available resources to continuously predict and address external threats that impact academic quality. Furthermore, emphasis should be placed on providing services using the latest electronic technologies.